Students' Knowledge Level About the Benefits of Sports at SMP Labschool UNTAD Palu - Fergiana Risky Cantika; Humaedi Humaedi; Muhammad Agusman; Muhammad Ismail (Journal of General Education and Humanities, 2025)
This study aims to measure junior high school students' knowledge at Labschool UNTAD Palu regarding the health benefits of exercise. This quantitative descriptive study uses a questionnaire comprising 25 statements across five dimensions of knowledge: Basic Knowledge, Physical Benefits, Mental and Social Benefits, Exercise Habits and Frequency, and Healthy Lifestyle. The questionnaire uses a 5-point Likert scale with the following anchors: Strongly Agree (SA), Agree (A), Neutral (N), Disagree (D), and Strongly Disagree (SD). The determination of knowledge level categories is based on a maximum total score range of 125, where the High category is set at a score range of 100–125 (80–100%), Medium at 75–99 (60–79%), and Low at a score of <75 (<60%). The results showed that the majority of students had a knowledge level in the High category (75% of students). In general, the average total score was 102.5 out of 125, indicating a good understanding of the benefits of exercise across physical, mental, and social perspectives. However, item-by-item analysis found that consistency of behaviour, particularly in the exercise frequency indicator, had the lowest average score (3.75) among all items. The practical implication is that physical education programs need to strengthen the integration between cognitive awareness and behavioural habits, particularly by improving motivational strategies so that students can apply consistency and frequency in exercising regularly.